Genetic Control of Capsid Length in Bacteriophage T4 I. Isolation and Preliminary Description of Four New Mutants - Doermann, A. H. (1973)
Four new mutants are described whose phenotypic expression affects the length of the head of bacteriophage T4D. All mutants produce some phenotypically normal phage particles. Mutant pt21-34 also produces at least two size classes of phage particle which have heads that are shorter than normal. The other three mutants, ptg19-2, ptg19-80, and ptg191, produce, in addition to phages with normal and with shorter-than-normal heads, giant phages with heads from 1.5 to at least 10 times the normal length. All mutations are clustered near gene 23. Giant phage particles have the following properties: they are infectious and contain and inject multiple genomes as a single continuous bihelical DNA molecule of greater-than-unit length. Their frequency, relative to the total plaque-former population, increases late in the infectious cycle. They have a normal diameter, variable length, and a buoyant density range in CsCl from equal to slightly greater than that of normal phage. The arrangement of capsomers is visible in the capsids, which are composed of cleaved gene 23 protein.